Overview of the Functions of Ginger Rhizome (Zingiber officinale Roscoe), Black Cumin (Nigella sativa), and Pasak Bumi (Eurycoma longifolia Jack) in Male Infertility - Setyaningrum, Dyah Ayu Woro; Anggraini, Kirana (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2023)
Background: More than 186 million individuals worldwide from Southeast Asian and African nations are affected by infertility, a common health issue, specifically among men. In Indonesia, the use of